Revised growth charts for children with down syndrome. (24th May 2012) - McGowan, M; Marder, E; Dennis, J; Wright, C; Cole, T; Short, J; Ellis, J
Abstract : Growth charts are widely used in health care settings throughout the world in order to monitor children's growth. Changes in the growth pattern can be an early indicator of medical problems. Children with Down syndrome differ from typically developing children in their growth patterns, so it is helpful for their measurements to be plotted on specific charts that have been standardised on a population of children with the syndrome. In 2002 our group produced new charts using data collected from 1100 healthy children with Down syndrome in the UK and Ireland (6000 measurements). In 2011 these charts were revised and re-issued in a new format which closely mirrors the 2009 UK-WHO charts. New methods of statistical analysis have been employed to calculate the growth curves. These charts incorporate a number of new features including: ▶ Revised advice about monitoring the growth of preterm babies. ▶ Head circumference growth lines extended to age two. ▶ A specially designed "BMI look-up chart" providing information about assessing overweight. ▶ "Low lines" for exceptionally small children, which can be used to monitor the growth of children who have had serious medical problems that may have affected their growth. Copies of these charts are included in a new version of the specific Down syndrome supplement for the UK Personal Child Health Record launched in 2011. Members of the Growth Chart Committee of the RCPCH have worked closely with us on this project. The charts have been available commercially since June 2011 but feedback on the new format was collected up to the end of 2011. This has resulted in a number of revisions to the latest version, which will now carry the logos of both the Down Syndrome Medical Interest Group and the RCPCH, and which will be available at the RCPCH Spring meeting. By presenting it at this meeting we hope to bring it to the attention of a wide audience.